Electrical capacitance tomography (ECT): an improved sensitivity distribution using two-differential excitation technique - Mohamad, Elmy Johana; Mohmad Ameran, Hanis Liyana; Abdul Rahim, Ruzairi; Marwah, Omar Md. Faizan (Penerbit UTM Press, 2015)
In this study, we propose the use of the two-differential potential excitation technique in an Electrical Capacitance Tomography (ECT) system to improve: (1) the non-uniform sensitivity distribution caused by the non-uniform potential distribution in the central area; and (2) the nonlinear relation between capacitance and material permittivity. A simulation of a 16-segmented ECT system is developed using COMSOL Multiphysics to observe the changes of the inter-electrodes capacitances and the permittivity of the dielectric material when two differential excitation potentials are injected. Generated phantoms and measured values are presented. An experiment using the real system is also carried out to verify the simulations results. By using this technique, it was shown that the relationship between the capacitances measured from inter-electrodes and the permittivity became more linear. In addition, potential distribution is increased in the central area indicating an increase in the sensitivity distribution in the central area. The use of this technique increases the level of detected signals and improves the SNR (signal-to-noise ratio) as compared to those achieved using standard single-voltage source methods.